Unpacking the Complexities of Energy Renovation Programs for Family Houses: Case Study of Croatia - Šostar, Marko; Škoko, Ines (International Journal of Energy Economics and Policy, 2024)
This study investigates the impact of administrative barriers on the financing of energy renovation of family homes in the Republic of Croatia. The research aims to prove a causal relationship between the limitations of the support system and citizen satisfaction with the existing support system for energy renovation of family homes, which directly affects an individual’s motivation to apply for a competition. A survey was conducted on 308 respondents, and mathematical methods were used to determine the impact. The research results show that different factors have varying degrees of influence on the perception of family homeowners and their decision to apply for a project, and that this perception depends on age, employment status, and monthly income of the individual.